Minimally invasive resection of brain metastases. (12th October 2019) - Phang, Isaac; Leach, John; Leggate, James; Karabatsou, Konstatina; Coope, David; D'Urso, Pietro
Abstract: Minimally invasive resection of brain metastases aims to maximize resection while minimizing brain trauma. Patients with one or more metastases resection following neuro-oncology multidisciplinary meeting discussion from Sep 2014 to Oct 2018 with pre- and post-operative MRI were included. All patients including posterior fossa metastases or multiple metastases were positioned supine. Hair was not shaved. Volumetric post-contrast T1 MRI was used for incision planning and neuronavigation. The craniotomy site was tailored to tumor depth according to keyhole principles and ranged between 2 to 3cm. Intraoperative monitoring and awake mapping were carried out in selected cases. Out of 320 consecutive patients with brain metastases, 44 patients were identified as suitable for minimally invasive resection. 9 had no post-operative imaging and were excluded. There were 39 metastases in 35 patients. There were 18 cerebellar metastases, 9 frontal, 5 parietal, 3 occipital, 2 temporal, 1 intraventricular and 1 basal ganglia. Median length of stay was days (range: 1 – 24). Average tumor volume was 54.7cm 3 (range: 10 – 240cm 3 ). Endoscopic assistance was used in 4 patients. Median performance status improved from 2 to 1(range: pre-operative: 0 – 4; post-operative: 0 – 2). Median survival was 14.7 months. Minimally invasive resection of brain metastasis is safe and effective and in selected cases confers advantages compared to standard techniques.